Investigation of Poor Prognostic Factors Among Rheumatoid Arthritis Patients in Turkbio Registry - Inanc, Nevsun; Erturk, Zeynep; Ozen, Gulsen; Dalkilic, Ediz; Koca, Suleyman Serdar; Can, Gercek; Onen, Fatos (Wiley, 2017)
[Abstract Not Available]
81st Annual Meeting of the American-College-of-Rheumatology (ACR) / Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 03-08, 2017 -- San Diego, CA